Could conservation tillage increase the resistance to drought in Mediterranean faba bean crops? - Madejón, Paula; Fernández-Boy, Elena; Morales-Salmerón, Laura; Navarro-Fernández, Carmen M.; Madejón, Engracia; Domínguez, María Teresa (Agriculture, ecosystems & environment, 2023)
Climate change, especially in Mediterranean countries, might have a detrimental effect on agro‑ecosystems and agricultural production, as well as on the price, quantity and quality of the products. This study assesses the potential impact of drought predictions on a faba bean crop, and evaluates the adoption of conservation tillage practices to reduce this effect. For this purpose, a rainfall exclusion experiment was carried out in a Mediterranean rotation in Southwest Spain, where a long-term tillage experiment was running since 2008. Soil water storage (SWS), crop productivity and mineral nutrition, plant ecophysiology and biomass quality, as well as the colonization of roots by arbuscular mycorrhizal fungi (AMF) and symbiotic Rhizobium bacteria were evaluated over one growth cycle to study the combined effect of different tillage systems - non-tillage (NT), reduced tillage (RT) and traditional tillage (TT)- and rainfall reduction. Rainfall reduction had a negative impact on faba bean germination on the TT system, and on its aboveground biomass across the three tillage systems, but did not affect grain production. The percentage of biomass yield reduction by rainfall exclusion was 30% for NT, 50% for RT and 20% for TT. In the case of RT, low yields were influenced by a high incidence of weeds under rainfall reduction. The negative effect of water exclusion was especially evident on photosynthesis rates and stomatal conductance across all tillage types, while leaf water potential was affected by drought only in the TT system. These ecophysiological indicators were positively associated to some variables of arbuscular mycorrhizal colonization and Rhizobium nodulation in roots. Changes in the patterns of symbiotic interactions in response to drought depended on the tillage type. We conclude that, despite no effect on soil water storage, in the conservation tillage systems the increase in the mycorrhizal colonization in roots, particularly under NT, could be beneficial for plants to face drought stress. However, in a scenario of reduced rainfall it will be necessary to invest more resources in weed control under RT. [Display omitted] •Rainfall exclusion reduces faba bean yield regardless of the tillage.•Plant physiological parameters are positively affected by conservation tillage.•AMF colonization in conservation tillage could be beneficial for plants to face drought stress.•Conservation tillage can confer stability to droughts in faba bean if weeds are under control.